Hubungan Aktivitas Fisik Dengan Kualitas Tidur Pada Santriwati Pondok Pesantren Darul Hijrah Puteri - Sofiah, Siti; Rachmawati, Kurnia; Setiawan, Herry (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Most adolescent have problems in the quality of sleep caused by fatigue as a result of irregular physicalactivity. This research to determine the relationship between physical activity with sleep quality for femalestudents at “Darul Hijrah Puteri” Islamic Boarding School. The design of this study was analytic surveywith cross sectional approach design. The study population was 484 female students. Cluster randomsampling is a technique used in sampling so that 243 respondents were obtained. Data were analyzed usingChi-Square test. The instrumentxof thisxstudy usedxaxquestionnaire. The results showed (p-value = 0. 384>0.05) that there was no relationship between physical activity and sleep quality in female students of theDarul Hijrah Islamic Boarding School in Martapura. There are several factors affect sleep quality, so thephysical activity cannot be the only factor for causing sleep quality problems.